Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.527
|View full text |Cite
|
Sign up to set email alerts
|

Wikidatians are Born: Paths to Full Participation in a Collaborative Structured Knowledge Base

Abstract: We investigated how participation evolves in Wikidata as its editors become established members of the community. Originally conceived to support Wikipedia, Wikidata is a collaborative structured knowledge base, created and maintained by a large number of volunteers, whose data can be freely reused in other contexts. Just like in any other online social environment, understanding its contributors' pathways to full participation helps Wikidata improve user experience and retention. We analysed how participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…The distribution of author and publisher types for references did not match Wikipedia [9], despite the partial overlap of the two communities [20]. Almost no news sources are used as sources in Wikidata, compared to the online encyclopedia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of author and publisher types for references did not match Wikipedia [9], despite the partial overlap of the two communities [20]. Almost no news sources are used as sources in Wikidata, compared to the online encyclopedia.…”
Section: Discussionmentioning
confidence: 99%
“…While most work around Wikidata focuses on the quality of its triples [4] or analyses its community dynamics [20], to the best of our knowledge no studies have investigated provenance quality. Little is known about the quality of the sources included to support claims, although this is a key issue for Wikidata.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning tenure, previous work [24] has shown that Wikidata editors change the focus and scope of their activity as they gain experience within the system. This suggests that users with different levels of experience may bring complementary skills in building high-quality items.…”
Section: Group Diversity and Outcome Qualitymentioning
confidence: 99%
“…This suggests that users with different levels of experience may bring complementary skills in building high-quality items. Editor activity may also vary along their edit scope [24]. Some users carry out similar tasks, i.e.…”
Section: Group Diversity and Outcome Qualitymentioning
confidence: 99%
See 1 more Smart Citation